Gender-dependent resiliency to stressful and metabolic challenges following prenatal exposure to high-fat diet in the p66Shc−/− mouse - Bellisario, Veronica; Berry, Alessandra; Capoccia, Sara; Raggi, Carla; Panetta, Pamela; Branchi, Igor; Piccaro, Giovanni; Giorgio, Marco; Pelicci, Pier G.; Cirulli, Francesca (Frontiers in Behavioral Neuroscience, 2014)
Metabolic stressful challenges during susceptible time windows, such as fetal life, can have important implications for health throughout life. Deletion of the p66Shc gene in mice leads to reduced oxidative stress (OS), resulting in a healthy and lean phenotype characterized by increased metabolic rate, resistance to high-fat diet (HFD)-induced obesity and reduced emotionality at adulthood. Here we hypothesize that p66Shc−/− (KO) adult offspring might be protected from the detrimental effects induced by maternal HFD administered before and during pregnancy. To test such hypothesis, we fed p66Shc+/+ (WT) and KO females with HFD for 13 weeks starting on 5 weeks of age until delivery and tested adult male and female offspring for their metabolic, neuroendocrine, and emotional profile. Prenatal diet affected stress responses and metabolic features in a gender-dependent fashion. In particular, prenatal HFD increased plasma leptin levels and decreased anxiety-like behavior in females, while increasing body weight, particularly in KO subjects. KO mice were overall characterized by metabolic resiliency, showing a blunted change in glycemia levels in response to glucose or insulin challenges. However, in p66Shc−/− mice, prenatal HFD affected glucose tolerance response in an opposite manner in the two genders, overriding the resilience in males and exacerbating it in females. Finally, KO females were protected from the disrupting effect of prenatal HFD on neuroendocrine response. These findings indicate that prenatal HFD alters the emotional profile and metabolic functionality of the adult individual in a gender-dependent fashion and suggest that exposure to high-caloric food during fetal life is a stressful condition interfering with the developmental programming of the adult phenotype. Deletion of the p66Shc gene attenuates such effects, acting as a protective factor.